POLICY IMPLEMENTATION EVALUATION TOWARD UNDERGROUND WATER MANAGEMENT BASED ON LOCAL GOVERNMENT REGULATION NO. 10 OF 2002*) - Irmawatty Paula Tamburaka (Jurnal Green Growth dan Manajemen Lingkungan, 2013)
The objective of this research in aim at finding out the information related to the implementation of Local Government Regulation No.10 2002 obout underground water management. The research finding reveal that this regulation has been well implemented based on data which collected by applying interview. Most of Bekasi people stuted that information about this regulation formal from other people and well socialized by local goverment in change of.